Collecting duct (Bellini duct) renal cell carcinoma: a clinical case and literature review - N. I. Sorokin; V. E. Sinitsyn; O. A. Kharlova; A. A. Strigunov; O. Yu. Nesterova; R. A. Nikoghosyan; E. A. Galliamov; A. A. Kamalov (Вестник урологии, 2024)
A rare subtype of renal cell carcinoma (RCC) is Bellini collecting duct carcinoma, also known as medullary renal carcinoma or distal nephron carcinoma, which accounts for 0.4-2.0% of all RCC cases. This subtype has the poorest prognosis of all RCC subtypes, typically presenting as a low-grade tumor at the pT3 or higher stage. Consequently, many patients have distant metastases at diagnosis and 60% develop metastases following radical treatment. There have been approximately 400 literature-reported cases of Bellini ductal carcinoma to date. We present a case report of a patient with early-stage Bellini duct cancer and a literature review of published reports on this condition.